The presence of baseline HBsAb-Specific B cells can predict HBsAg or HBeAg seroconversion of chronic hepatitis B on treatment - Shengxia Yin; Yawen Wan; Rahma Issa; Yijia Zhu; Xiaoming Xu; Jiacheng Liu; Minxin Mao; Ming Li; Xin Tong; Chen Tian; Jian Wang; Rui Huang; et al. (Emerging Microbes and Infections, 2023)
Indices for predicting HBsAg or HBeAg seroconversion in patients with chronic hepatitis B virus (HBV) infection during antiviral therapy remain elusive. We aimed to investigate if the presence of HBsAb-specific B cells at baseline can predict HBsAg or HBeAg seroconversion. In this study, 134 treatment-naive patients with chronic HBV were enrolled. A baseline HBsAb-specific B cell ELISpot assay was performed for all the patients that enrolled. Serum samples were collected at 12, 24, and 48 weeks for patients treated with Peg-IFN-α, or at 1 year, 3 years, and 5 years for patients treated with NAs. Laboratory testing of HBsAg, HBsAb, HBeAg, HBeAb, HBcAb, HBV DNA, ALT, and AST was done. We observed a significantly lower frequency of HBsAb-specific B cells in patients with chronic HBV than in healthy individuals . In the Peg-IFN-α-treated group, 41.2% of patients with baseline HBsAb-specific B cells achieved HBsAg seroconversion, while only 13.6% of patients without baseline HBsAb-specific B cells achieved HBsAg seroconversion (p = 0.006). By logistic regression analysis, patients with baseline HBsAb-specific B cells and HBsAg ≤ 1500 had higher HBsAg clearance at the end of treatment (p < 0.05). In the NA-treated group, 58.3% of patients with baseline HBsAb-specific B cells achieved HBeAg seroconversion, whereas only 30.0% of patients without baseline HBsAb-specific B cells achieved HBeAg seroconversion (p = 0.114). Our result revealed that baseline HBsAb-specific B cells by ELISpot assay might be a valuable predictive biomarker of HBsAg or HBeAg seroconversion in patients with chronic HBV on treatment.